Empowering Women Farmers Groups to Enhance Community Social Assets: A Case Study in Sobokerto Village, Boyolali - Fitri; Hadiyati, Afina Rahma; Setiawan, Wisnu; Negoro, Abdul Rafi' Damar; Prihatin, Silverius Djuni; Fatonah, Siti; Mahendra, Dewangga Cipta (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Ngudi Makmur and Bangun Sejahtera Women Farmers Groups are CSR-funded groups of PT Pertamina Patra Niaga AFT Adi Sumarmo implemented in Sobokerto Village, Ngemplak District, Boyolali Regency. The implementation of the KWT program aims to increase economic potential and human resources and increase social assets in the community. This research uses descriptive qualitative methods with data extraction by in-depth interviews and observations. The source of data in this research is secondary data obtained from intermediaries through print media, journals, youtube and so on which represent data on the CSR Implementation Program of PT Pertamina Patra Niaga AFT Adi Sumarmo. This research uses the foundation of Sustainable Development Theory to see the implementation of the program to answer community needs in increasing the social assets of the PT Pertamina Patra Niaga AFT Adi Sumarmo fostered group in carrying out community empowerment. The results of this study have an impact on sustainable development that affects social change in the fulfillment of community social assets, in the form of creating collective movements and social cohesion.